A dedicated automated injection system for dynamic contrast‐enhanced MRI experiments in mice. Issue 3 (21st September 2012) - Sedlacik, Jan; Myers, Adrianne; Loeffler, Ralf B.; Williams, Regan F.; Davidoff, Andrew M.; Hillenbrand, Claudia M.
Abstract Purpose: To develop a reproducible small‐animal dynamic contrast‐enhanced (DCE) MRI set‐up for mice through which volumes <100 μL can be accurately and safely injected and to test this set‐up by means of DCE measurements in resting muscle and tumor tissue. Materials and Methods: The contrast agent (CA) injection system comprised 2 MR‐compatible syringe pumps placed 50 cm from the 7T magnet bore where the fringe field is approximately 40 mT. Microbore tubing and T‐connector, close to the injection site, minimized dead volume (<10 μL). For DCE‐MRI measurements in 8 CB‐17 SCID mice with 1500–2500 mm3 large orthotopic neuroblastoma, a bolus of 10‐fold‐diluted Gd‐DTPA CA solution (0.1 mmol/kg) was delivered (5 μL/s), followed by a 50‐μL saline flush. Retro‐orbital injections were given instead of tail vein injections, because the peripheral vasculature was reduced because of large tumor burden. Results: The CA injection was successful in 19 of 24 experiments. Optical assessment showed minimal dispersion of ink‐colored CA bolus. Mean (±SD) pharmacokinetic parameters retrieved from DCE‐MRI examinations in resting muscle (Ktrans = 0.038 ± 0.025 min−1, kep = 0.66 ± 0.48 min−1, ve = 0.060 ± 0.014, vp = 0.033 ± 0.021) and tumor (Ktrans = 0.082 ± 0.071 min−1, kep = 0.82 ± 0.80 min−1, ve = 0.121 ± 0.075, vp = 0.093 ± 0.051) agreed with those reported previously. Conclusion: We successfully designed and implemented a DCE‐MRI set‐up system with short injection lines and low dead volume. The system can be used at any field strength with the syringe pumps placed at a sufficiently low fringe field (<40 mT). J. Magn. Reson. Imaging 2013;37:746–751. © 2012 Wiley Periodicals, Inc.